RIGHT OF THE CHILD TO INFORMATION ACCORDING TO THE DIRECTIVE 2016/800/EU ON PROCEDURAL SAFEGUARDS FOR CHILDREN WHO ARE SUSPECTS OR ACCUSED PERSONS IN CRIMINAL PROCEEDINGS (EU and comparative law issues and challenges series (ECLIC), 2018)
One of the elements that is often neglected in cases when children are suspects or accused persons in criminal proceeding is the fact that children and their parents almost always lack information about their rights during criminal proceeding. Children in that situation face a higher risk of deprivation of their fundamental procedural rights because of their young age, lack of knowledge, their incomplete physical and psychological development, and emotional immaturity. One of the guarantees of the right to a fair trial (article 6 ECHR) that has been developed in the ECtHR jurisprudence is the right to effectively participate in criminal proceeding, but to accomplish that in practice the judicial system first needs to ensure that children are informed in a child-friendly manner what rights they have during criminal proceeding and how they can exercise them. Directive EU 2016/800 sets a minimum number of rules on several procedural rights for children in criminal proceedings, including the right to information (article 4 and 5), in order to ensure a higher standard of protection for children as suspects or accused persons. This paper analyses the right to information according to the Directive EU 2016/800 and other international and regional documents and how this right is regulated in some EU Member States, whether special provisions are applied to children, with special reference to the legislation of the Republic of Croatia. The aim of this paper is to give an overview of how the right to information is regulated in the Directive 2016/800 (EU) and in EU Member States in order to offer new legal solutions (de lege ferenda) for implementation of this right in Croatian juvenile criminal legislation.